Vocational Self-Estimates and Perceived Competencies of Native High School Students: Implications for Vocational Guidance Counselling - Krebs, Elfie; Hurlburt, Graham; Schwartz, Carl (Canadian Journal of Counselling and Psychotherapy, 2011)
The present study compared the vocational self-estimates and competencies of native to nonnative students. Results showed that native students had less confidence in their vocational skills and their employment opportunities. The authors discuss the implications of these findings and detail a number of suggestions to improve native student confidence.